Gerakan Literasi Fisik Anti Malas Bergerak di Sekolah Master Indonesia - Bachtiar, Farahdina; Agustiyawan, Agustiyawan; Wibisono, Heri; Kurniawan, Andi; Adriani, Aqilla; Dzakira, Faiza Syifa (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
The younger generation, as the nation's future, must receive special attention, particularly regarding health. The health development of children and adolescents significantly impacts a country's resilience. One approach to enhancing physical activity in schools is through the concept of physical literacy. Similar to general literacy, physical literacy aims to raise awareness and understanding of the importance of physical activity for health. This concept is intended to be maintained throughout life and significantly influences an individual's participation in physical activities. Consequently, this community service program aims to foster physical literacy, increase awareness of the benefits of physical activity for health, and provide enjoyable physical activity experiences. The program was conducted at the Indonesian Master's School with 32 participants aged 12-15. Activities included the physical literacy assessment by filling out a questionnaire, anthropometric measurements, health education, gymnastics, games, providing a poster, and a follow-up plan in the form of health promotion through the digital platform. The results of physical activity assessment and evaluation through pre-test and post-test indicated that participants were aware of the importance of physical activity. Although awareness of physical activity is good among the majority of participants, the application of physical activity in daily life needs to be improved. In fact, Indonesian people tend to engage in low levels of physical activity, which can lead to increased rates of obesity as well as the risk of other non-communicable diseases (NCDs).